Appraisal, Work-Up and Diagnosis of Anterior Uveitis: A Practical Approach - Herbort, Carl P. (Medknow Publications, 2009)
This article presents a comprehensive approach of the diagnosis of anterior uveitis and appropriate investigational tests based on clinical signs. Uveitis has classically been presented by uveitis specialists as an obscure and complicated field in ophthalmology that was supposed to be restricted to the happy few who had the knowledge, which in some countries was even prevented from being diffused. The effect was that ophthalmologists turned away from uveitis or were not correctly armed when they chose to take care of uveitis patients. The consequences of this situation often fell upon the patients. Since more than 15 years our group has been represented by the Society for Ophthalmo-Immunoinfectiology in Europe (SOIE), which has been working to alter this image of uveitis and ensure that the knowledge of the basics of uveitis reaches the practicing ophthalmologist. Our firm believe is that up to 70% of uveitis cases, especially anterior uveitis, can be taken care of by the practicing ophthalmologist following a structured approach in the appraisal of the uveitis case. Judging from the attendance obtained, the response to our approach in every country (where we organise courses) has been inversely proportional to the previous disinterest since we started publicizing it.